Respons Agama terhadap Kemiskinan: Perspektif Sosiologi - Nurul Aeni (Jurnal Sosiologi Agama Indonesia (JSAI), 2021)
This article aims to provide an overview of the phenomenon of poverty from a sociological perspective, especially from the perspective of the sociology of religion. This article uses a literature review, which is a literature review that supports a particular problem that is being studied in depth. The data in this article were obtained from books, journals, articles, theses and other relevant literature. The results of this study indicate that sociological poverty is not only a personal phenomenon but also a social phenomenon. In the context of religion, Islam responds to the phenomenon of poverty by encouraging and encouraging people to work hard and share with each other.